2013
DOI: 10.1227/neu.0b013e318283c98b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic BoneScalpel for Osteoplastic Laminoplasty in the Resection of Intradural Spinal Pathology

Abstract: The BoneScalpel is a safe and technically feasible device for performing osteoplastic laminoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…4 This mechanism confers a relative selectivity to ultrasonic bone dissectors such that dense bone tissue is destroyed before and in preference to soft tissues (eg, dura and arterial wall), thus permitting safe bone removal adjacent to important soft tissue structures. [4][5][6][7] Moreover, the absence of a high-speed spinning burr in ultrasonic bone dissectors eliminates the possibility of unwanted soft tissue capture/injury and erratic drill movements. Finally, the microshaver bit of the ultrasonic bone dissector has a side-cutting surface (Figure 1), which makes it possible for the blunt tip and smooth back of the bit to come in brief contact with the nerve roots and vertebral artery without risk of injury, as demonstrated in this report.…”
Section: Discussionmentioning
confidence: 99%
“…4 This mechanism confers a relative selectivity to ultrasonic bone dissectors such that dense bone tissue is destroyed before and in preference to soft tissues (eg, dura and arterial wall), thus permitting safe bone removal adjacent to important soft tissue structures. [4][5][6][7] Moreover, the absence of a high-speed spinning burr in ultrasonic bone dissectors eliminates the possibility of unwanted soft tissue capture/injury and erratic drill movements. Finally, the microshaver bit of the ultrasonic bone dissector has a side-cutting surface (Figure 1), which makes it possible for the blunt tip and smooth back of the bit to come in brief contact with the nerve roots and vertebral artery without risk of injury, as demonstrated in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al 12 analysed 40 adult patients without achondroplasia undergoing laminoplasty utilising an ultrasonic bone scalpel. They recorded one case of incidental durotomy following use of the ultrasonic scalpel, and concluded that it was a safe and technically feasible device for use in adult laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…While Parker et al reported that an ultrasonic osteotome was safe and efficacious for use in laminectomies, no published study has reported its use in cranio-orbital applications [7]. We report our initial experience using an ultiasonic osteotome in two-piece orbitozygomatic craniotomies for tumor resection and comment on surgical outcome and complications as a result of its use.…”
Section: Introductionmentioning
confidence: 98%